2017
DOI: 10.3389/fnins.2017.00509
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study on the Dynamic EEG Center of Mass with Different References

Abstract: One of the most fundamental issues during an EEG study is choosing an available neutral reference. The infinity zero reference obtained by the reference electrode standardization technique (REST) has been recommended and used for its higher accuracy. This paper examined three traditional references, the average reference (AR), the linked mastoids reference (LM), and REST, in the study of the EEG center of mass (CM) using simulated and real ERPs. In the simulation, the relative error of REST was the smallest am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…Over the years, many researchers have provided evidence and advice on the choice of different reference electrodes. Simulation and experimental ERP studies with a visual oddball paradigm indicated that AR and LM (Linked Mastoids) may change the amplitude of P300 and distort the CM trajectory and its instantaneous velocity, while REST continues to provide objective results (Qin et al, 2017 ). A large-scale brain network simulation analysis compared REST with Fz, Oz, LM and AR and showed that the relative errors followed the pattern REST < AR < LM < (Fz, Oz), which indicated that REST was a potentially preferable reference (Lei and Liao, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the years, many researchers have provided evidence and advice on the choice of different reference electrodes. Simulation and experimental ERP studies with a visual oddball paradigm indicated that AR and LM (Linked Mastoids) may change the amplitude of P300 and distort the CM trajectory and its instantaneous velocity, while REST continues to provide objective results (Qin et al, 2017 ). A large-scale brain network simulation analysis compared REST with Fz, Oz, LM and AR and showed that the relative errors followed the pattern REST < AR < LM < (Fz, Oz), which indicated that REST was a potentially preferable reference (Lei and Liao, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The physical basis of this operation is that the potentials before and after conversion are all derived from the actual neural electrical activity source in the brain (Hu et al, 2018 ). Although different reference electrodes have been investigated in many studies (Ferree, 2006 ; Nunez and Srinivasan, 2006 ; Huang et al, 2017 ; Lei and Liao, 2017 ; Qin et al, 2017 ), most of them are based on model simulated data; it is still unclear what the accurate estimation of the differences is for real EEG recordings in various experimental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Some previous studies compared the three different references method by using simulated dipoles and real EEG data. And the results of simulated data showed that through all the EEG frequency bands including theta, delta, alpha, beta, the features, like power spectra (Trujillo et al, 2017 ), non-linear features (Chella et al, 2017 ), the different network connectivity structures, such as default mode network (Qin et al, 2010 ), the EEG center of mass (Qin et al, 2017 ), sensor level functional connectivity graphs (Huang et al, 2017 ), the large-scale brain network (Lei and Liao, 2017 ), obtained from the REST were more accurate than other references. For real EEG data, there were significant differences existing in the statistics for REST and other references, for example, the ERPs in the audiovisual stimulus, REST changed in the experimental effect (Tian and Yao, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…One important drawback of the scalp analysis derives from the reference choice. It has been demonstrated that a non-neutral reference influences the voltage waveform, the voltage weighted by the spatial coordinates of all the channels spectral distribution, the coherence and the network analysis ( Qin et al, 2010 , 2017 ; Chella et al, 2016 ). To overcome these limitations, it has been proposed a reference electrode standardization technique (REST) that approximately transforms multichannel recordings with a scalp point into real EEG data using an infinity neutral reference ( Yao, 2001 ).…”
Section: Discussionmentioning
confidence: 99%